2015
DOI: 10.5194/amt-8-1157-2015
|View full text |Cite
|
Sign up to set email alerts
|

Improving satellite-retrieved aerosol microphysical properties using GOCART data

Abstract: Abstract. The Multi-angle Imaging SpectroRadiometer (MISR) aboard the NASA Earth Observing System's Terra satellite can provide more reliable aerosol optical depth (AOD) and better constraints on particle size (Ångström exponent, or ANG), sphericity, and single-scattering albedo (SSA) than many other satellite instruments. However, many aerosol mixtures pass the algorithm acceptance criteria, yielding a poor constraint, when the particle-type information in the MISR radiances is low, typically at low AOD. We i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…This approach has been and continues to be used (e.g., Koch et al, 2009;Bahadur et al, 2010;Chung et al, 2012;Buchard et al, 2015;Pan et al, 2015;Li et al, 2015). However, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been and continues to be used (e.g., Koch et al, 2009;Bahadur et al, 2010;Chung et al, 2012;Buchard et al, 2015;Pan et al, 2015;Li et al, 2015). However, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using only Level 2 retrievals of AAOD (i.e., for AOD 440 > 0.4) on a global scale (e.g., Koch et al, 2009;Bahadur et al, 2010;Chung et al, 2012;Buchard et al, 2015;Pan et al, 2015;Li et al, 2015) is likely to lead to significant overestimates of absorption in cleaner regions although it may be appropriate for conditions of high loading. Several different approaches of varying complexity have been developed to better represent absorbing aerosol for cleaner conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the Level 2 Version 22 product against ground-based observations from the Aerosol Robotic Network (AERONET) (Holben et al, 1998), including assessments of particle type retrievals, can be found in Kahn et al (2010) and Kahn and Gaitley (2015). The mixture type information in the MISR Version 22 aerosol product has been exploited by Li et al (2013) and Li et al (2015), for example, who used CCM in-formation to select from the complete set of passing mixtures to improve agreement with AERONET in the continental United States.…”
Section: Introductionmentioning
confidence: 99%
“…The retrieval error of GOCART AOD is relatively small in dust and pollution regions, but has a low bias of 30-40% for biomass burning aerosols (Chin et al, 2009). In North/Central America, GOCART AOD is approximately 2 times lower than MODIS (Chin et al, 2004) and MISR (Li, S. et al, 2015). The GOCART 3-D simulations used in this analysis are the same temporal and vertical resolutions as GEOS-Chem, but with higher horizontal resolution (1° latitude × 1.25° longitude).…”
Section: Data Descriptionmentioning
confidence: 98%